Effectiveness of Case Method Implementation in Pedagogical Learning of Students Across Study Programs: A Study on Multidisciplinary Courses in Indonesian - Alfan, Muhammad; Anggraini, Ade Eka; Dewi, Radeni Sukma Indra; Sari, Zihan Novita; Pahlevi, Mohammad Bintang Hadiansyah; Wati, Pulia; Wulansari, Ayu Anggraeni; Rani, Noorazi (LP. Ma'arif Janggan Magetan, 2025)
This study discusses students' passive participation, understanding challenges, and limitations in case-solving skills in Learning and Pedagogy lectures. This study aims to address critical gaps in pedagogical research and offer evidence-based recommendations for improving teaching practices across academic disciplines. This study uses a descriptive quantitative approach. The design used is pre-experimental with a one-shot case study model. This study involved two data collection techniques, namely questionnaires and structured observations. The population in this study were all students of Malang State University who took the Learning and Pedagogy course in the Odd Semester of the 2022/2023 academic year. The researcher selected the B1 Offering class by purposive sampling, with the following inclusion criteria: active students, attending all lecture meetings, and willing to fill out the questionnaire and take the posttest. The findings indicate that the application of the case method is effective, with a sig value of 0.000. In particular, students who scored above 75 showed an average posttest score of 83.5688. This underlines the positive impact of the case method in encouraging students' active participation and case-solving skills.